2005
DOI: 10.1007/s11248-005-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Transfer of Genetically Modified DNA from Feed to Animal Tissues

Abstract: In Europe, public and scientific concerns about the environmental and food safety of GM (Genetically Modified) crops overshadow the potential benefits offered by crop biotechnology to improve food quality. One of the concerns regarding the use of GM food in human and animal nutrition is the effect that newly introduced sequences may have on the organism. In this paper, we assess the potential transfer of dietderived DNA to animal tissues after consumption of GM plants. Blood, spleen, liver, kidney and muscle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 18 publications
6
54
1
3
Order By: Relevance
“…Although few have found recombinant DNA sequences in any organ or tissue sample from animals fed GM plants (EFSA, 2007), our results showed that small DNA fragments can also be detected in kids organs when mothers are fed GM soybean. Recombinant plant DNA has also been found by other authors as a rare event (Chowdhury et al, 2003a;Mazza et al, 2005;Sharma et al, 2006) in organs and tissues of animals fed GM feeds. On the contrary, studies aiming at verifying the presence of transgenic fragments in milk gave negative results.…”
Section: R E T R a C T E Dmentioning
confidence: 61%
See 2 more Smart Citations
“…Although few have found recombinant DNA sequences in any organ or tissue sample from animals fed GM plants (EFSA, 2007), our results showed that small DNA fragments can also be detected in kids organs when mothers are fed GM soybean. Recombinant plant DNA has also been found by other authors as a rare event (Chowdhury et al, 2003a;Mazza et al, 2005;Sharma et al, 2006) in organs and tissues of animals fed GM feeds. On the contrary, studies aiming at verifying the presence of transgenic fragments in milk gave negative results.…”
Section: R E T R a C T E Dmentioning
confidence: 61%
“…Indeed, the implications of DNA transfer from food containing GM plants to an organism is no higher as compared with DNA transfer from food containing the corresponding conventional plant (Mazza et al, 2005).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic plant DNA has been found by other authors [15][16][17][18][19] in organs and tissues from animals fed GM feeds. On the contrary, in trials carried out on dairy cows fed GM soybean [20], the chloroplast DNA fragments were detected in milk but no transgenic fragments were found.…”
Section: Discussionmentioning
confidence: 88%
“…A complexidade das discussões é decorrente de dois fatores principais: por um lado, a base de conhecimentos científicos sobre as implicações e os impactos da liberação em lar ga escala de plantas transgênicas para o cultivo comercial é ainda insuficiente; por outro lado, a questão das plantas transgênicas enseja uma abordagem inter e multidisciplinar, uma vez que os impactos são diferenciados, os conflitos de interesses são múltiplos e o diálogo apenas re centemente vem se tornando público 4,5 .…”
Section: Introductionunclassified